Xylobium Lindl. - Bogarín Chaves, Diego Gerardo (2022)
Xylobium derives from the Greek words xylon, wood, and bios, life, meaning “life on the wood or tree”. Though, it seems contradictory that Lindley chose a name referring to the epiphytic habit of the plant because the type species, D. squalens, was found “growing on the ground, not on trees”. However, he may have chosen this name in analogy with Dendrobium, which comes from the Greek dendro, tree, and bios, life, meaning “life on the tree”. In any case, Xylobium comprises mostly epiphytic plants, while other species grow on the ground, mainly among organic litter in understory vegetation.